IPTEKS PENGELOLAAN DANA DESA PADA DESA TUMALUNTUNG KECAMATAN KAUDITAN - Sondakh, Jullie J.; Nangoi, Grace B.; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2017)
Providing greater opportunities for villages to manage their own governance and equitable development implementation, with the enactment of Law Number 6 of 2014 concerning Villages, it is hoped that the village government will be more independent in managing the government and various natural resources, including financial management and wealth belonging to the village. This service aims to provide understanding to village officials about the cycle of village financial management, which starts from the planning and budgeting stages; implementation and administration; to reporting and accountability of village financial management. The specific target of this service is the making of the APB Village Implementation Realization Report and the APB Village Implementation Realization Accountability Report. In order to achieve this goal, this service uses lecture methods and technical training. Lecture to provide an initial understanding of village financial management, while technical training is training in preparing reports on the realization of village funds and accountability reports on the realization of village APB. The service plan was carried out with a preliminary survey to find out about village problems, in connection with the management of village funds, after which they conducted discussions with village leaders to collaborate, then preparation of materials and training to be presented to the village government.